Open Source 3D Game Engines For Serious Games Modeling (2012)
In this chapter we will review some tools and open source Game Engines used for modeling of real scenarios in serious games for training. One of the typical uses of serious games (3D serious games) is specialized training in dangerous tasks or when the training is quite expensive. However, typical games use artificial scenarios, created by artists and created according to the restrictions imposed by the Game engine used. In our experience, some tasks require the use of a real scenario like a city, forest area, etc, and most of this information is available as Digital Terrain Models in Geographic Information Systems (GIS). The problem here is that GIS formats are not compatible with 3D formats used in Game engines. Then we have to solve the problem of convert the GIS format to a 3D format supported by the Game Engine.